The Difference Of Pain Labour Level With Counter Pressure And Abdominal Lifting On Primigravida In Active Phase of First Stage Labor - Tuti Oktriani; Ermawati Ermawati; Hafni Bachtiar (Universitas Andalas, 2018)
Nowadays many methods are offered to reduce pain in labor, both pharmacological (using drugs) and non pharmacological methods. If possible the choice of non-pharmacologic therapy for the management of pain in pregnancy and labor should be considered before using analgesic drugs. One of an effective non-pharmacological method to reduce pain is with massage. The basis of this theory is the gate control theory proposed by Melzak and Wall (Lliadou, 2009).This study aimed to analyze diference of pain relief on active phase of labour with Counter Pressure and abdominal Lifting. This was an experimental with pre test and post test design. The samples were 42 women on their active phase of labor, 21 women for counter Pressure technic and 21 women for Abdominal Lifting technic. Counter Pressure technic decreased pain of labor with a P-value 0.015 (p<0.05) and abdominal lifting technic significantly decreased pain of labour with a P-value 0.001. Abdominal lifting technic (P 0,001) more effective than counter pressure technic (P 0,015) for pain relief in active phase of labour.